How Safe Is It to Rely on Macrolophus pygmaeus (Hemiptera: Miridae) as a Biocontrol Agent in Tomato Crops? - Sanchez, Juan A.; López-Gallego, Elena; Pérez-Marcos, María; Perera-Fernández, Luis G.; Ramírez-Soria, María J. (Frontiers in Ecology and Evolution, 2018)
Omnivorous mirids (Hemiptera: Miridae) are unusual as biocontrol agents, as they feed on both plants and pests. Therefore, extensive knowledge of their ecological behavior is required to maximize their predatory side and to minimise crop damage. Macrolophus pygmaeus is a known predator of small arthropods, used in European tomato crops for more than 20 years. This mirid is currently considered harmless to tomato, although some controversy remains in relation to the status of the species. The aim of this work was to investigate the benefits that M. pygmaeus provides as a predator and the likely damage as a plant feeder. The experiment was carried out in 6 experimental greenhouses in southern Spain. Two treatments, low and high M. pygmaeus populations, were assayed in a complete factorial randomized design with three replicates. Low and high M. pygmaeus populations were achieved by direct and pre-plant release methods, respectively. Tomato plants with a lower number of M. pygmaeus had a significantly higher number of whiteflies and Tuta absoluta galleries than those with a higher number of the mirid, and vice versa. A significantly higher proportion of aborted flowers and fruits was registered in greenhouses with higher M. pygmaeus numbers. Yield was also lower in greenhouses with higher mirid populations. The number of fruits harvested did not differ between treatments, but average fruit weight was significantly lower in the greenhouses with higher mirid numbers. The number of punctures attributed to M. pygmaeus on fruits were low in general and slightly higher in the treatment with more mirids. This work shows that M. pygmaeus provides both "services", as an efficient biocontrol agent of key pests in tomato crops, and "disservices", as it feeds on the reproductive organs of tomato plants, reducing yield. A deeper understanding of the factors that modulate the zoophytophagous response of this economically important species is needed.